RNA quantification using gold nanoprobes - application to cancer diagnostics - Conde, João (2020)
Molecular nanodiagnostics applied to cancer may provide rapid and sensitive detection of cancer related molecular alterations, which would enable early detection even when those alterations occur only in a small percentage of cells. The use of gold nanoparticles derivatized with thiol modified oligonucleotides (Au-nanoprobes) for the detection of specific nucleic acid targets has been gaining momentum as an alternative to more traditional methodologies. Here, we present an Au-nanoparticles based approach for the molecular recognition and quantification of the BCR-ABL usion transcript (mRNA), which is responsible for chronic myeloid leukemia (CML), and to the best of our knowledge it is the first time quantification of a specific mRNA directly in cancer cells is reported. This inexpensive and very easy to perform Au-nanoprobe based method allows quantification of unamplified total human RNA and specific detection of the oncogene transcript. The sensitivity settled by the Au-nanoprobes allows differential gene expression from 10 ng/μl of total RNA and takes less than 30 min to complete after total RNA extraction, minimizing RNA degradation. Also, at later stages, accumulation of malignant mutations may lead to resistance to chemotherapy and consequently poor outcome. Such a method, allowing for fast and direct detection and quantification of the chimeric BCR-ABL mRNA, could speed up diagnostics and, if appropriate, revision of therapy. This assay may constitute a promising tool in early diagnosis of CML and could easily be extended to further target genes with proven involvement in cancer development.